2018
DOI: 10.3748/wjg.v24.i43.4939
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrence of primary sclerosing cholangitis after liver transplantation is associated with de novo inflammatory bowel disease

Abstract: AIMTo evaluate risk factors for primary sclerosing cholangitis (PSC) recurrence (rPSC) after orthotopic liver transplantation (OLT) in patients with well-preserved colons.METHODSWe retrospectively evaluated the medical records of all patients transplanted for PSC in our center between July 1994 and May 2015 and selected 47 with follow-up of at least 60 mo for further analysis based on strict inclusion and exclusion criteria. rPSC was confirmed by magnetic resonance or endoscopic retrograde cholangiopancreatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Although many studies have examined the risk factors, it is unclear why rPSC develops post-LT. One of the main risk factors is IBD, as demonstrated with the decreased frequency of rPSC following colectomy prior to LT [128] . Others have reported that the presence of ulcerative colitis post-LT is significantly associated with the development of rPSC [129] . In those without a prior history of ulcerative colitis, the development of de novo colitis increases the risk considerably [130] .…”
Section: Pathogenesis and Risk Factors For Recurrent Pscmentioning
confidence: 98%
See 1 more Smart Citation
“…Although many studies have examined the risk factors, it is unclear why rPSC develops post-LT. One of the main risk factors is IBD, as demonstrated with the decreased frequency of rPSC following colectomy prior to LT [128] . Others have reported that the presence of ulcerative colitis post-LT is significantly associated with the development of rPSC [129] . In those without a prior history of ulcerative colitis, the development of de novo colitis increases the risk considerably [130] .…”
Section: Pathogenesis and Risk Factors For Recurrent Pscmentioning
confidence: 98%
“…Immunosuppression: Cyclosporine use decreased risk as compared to tacrolimus [110][111][112]107,110] Genetic predisposition [108] Increased donor age, warm and cold ischemic time [109,112,114] Preventative use of UDCA, and in combination with cyclosporine, post LT reduced the risk of rPBC [115] rPSC 20% to 25% [2] Diagnosis of PSC prior to LT and cholangiography showing non-anastomotic intrahepatic and/or extrahepatic bile duct strictures with irregularities and beading occurring more than 90 days post-LT Or Liver biopsy demonstrating fibrous cholangitis and/or fibro-obliterative lesions [127] Inflammatory bowel disease [128][129][130] Acute cellular rejection [131,132,134,135] Donor-recipient CMV mismatch [133] Poor graft quality [133] Pre-transplant MELD > 24 [133,135] Cholangiocarcinoma [134,135] Higher donor age [134] No proven therapies Symptomatic management ALT: Alanine aminotransferase; AST: aspartate transaminase; CMV: cytomegalovirus; MELD: model for end stage liver disease; MMF: mycophenolate mofetil; UDCA: ursodeoxycholic acid.…”
Section: Incidence and Diagnosis Of Aih Recurrencementioning
confidence: 99%
“…IBD in general and UC in particular are associated with concomitant PSC, for which the mainstay of treatment is OLT. This is probably the reason for encountering higher number of OLT than SOT of other organs in the IBD population[ 159 , 160 ]. The incidence risk of developing de novo IBD in SOT recipients versus general population is 206 and 20 respectively per 100000 person-years[ 161 ].…”
Section: Post-transplant Secondary Ibdmentioning
confidence: 99%
“…In a retrospective chart review of 6800 liver and/or kidney transplant recipients that received some form of immunosuppression, it was found that 14 individuals developed de novo IBD[ 161 ]. Post-OLT patients who develop de novo IBD had a tendency to have underlying PSC or develop PSC in the future[ 160 , 163 ].…”
Section: Post-transplant Secondary Ibdmentioning
confidence: 99%
“…Regarding rPSC, in one study which had all HLA data available for all donors and recipients, HLA-DRB1*08 allele was detected in either donor or recipient with rPSC [ 32 ]. On the other hand, in the study by Bajer et al, HLA-DRB1*07 in the donor represented a potential risk factor for rPSC [ 33 ]. For rNASH, G-allele in position rs738409 of patatin-like phospholipase domain-containing protein 3 (PNPLA3) presence in the recipient was associated with an increased hepatic concentration of triglycerides and with rMASH, though liver biopsy to confirm the diagnosis was only available in a minority of patients and recurrent disease diagnosis was based on biological and clinical criteria [ 34 ].…”
Section: Resultsmentioning
confidence: 99%